Acitretin heals pityriasis rubra pilaris but triggers itching. - Garofalo, L. (European Journal of Pediatric Dermatology, 2018)
The case of our patient case can be classified as pityriasis rubra pilaris type III, classical juvenile onset form. The diagnosis was confirmed by the clinical findings and biopsy. There are numerous treatments for pityriasis rubra pilaris (2): our case confirmed the insensitivity to corticosteroid therapy. The sensitivity of the disease to retinoids and to acitretin in particular has given conflicting results, sometimes excellent results as in our case, other times poor. According to some Authors (1), isotretinoin is more effective in children. However, the peculiarity of our case consists in the significant worsening of pruritus that contrasted with the rapid improvement of the disease and significantly reduced the quality of life of the child. In the literature we did not find any other cases that underline this side effect of acitretin in the treatment of pityriasis rubra pilaris.